Feminist Paradigm in the Study of Islamic Family Law In Indonesia - Fitriyani, Fitriyani (Scientia: Jurnal Hasil Penelitian, 2025)
This article examines the feminist approach in the context of Islamic family law in Indonesia, aiming to analyze how a feminist perspective can provide a critical view of the existing practice and interpretation of family law. This research was conducted through a library research method with a qualitative approach, exploring various academic literature, legal documents, and related sources, using descriptive analysis techniques. The results of the study indicate that the feminist paradigm makes a significant contribution to dismantling the patriarchal structure that has dominated the interpretation of Islamic family law. This article identifies several key areas where a feminist perspective can provide transformation, including: 1) Criticism of the concept of hierarchical family, 2) Re-reading the concept of polygamy and divorce, 3) Emphasis on equal rights and obligations of husband and wife, and 4) Deconstruction of textual interpretations that are detrimental to women. Methodologically, this study uses a feminist hermeneutic approach that considers the social, historical, and cultural contexts in re-reading religious texts. This allows for a more gender-responsive and equitable interpretation of Islamic family law.